1961
DOI: 10.1002/bbpc.19610650509
|View full text |Cite
|
Sign up to set email alerts
|

Zum Halbleiterverhalten des Nickeloxyds

Abstract: Es werden Ergebnisse von Thermospannungs‐ und Leitfähigkeitsmessungen an undotiertem NiO, an mit 0,05‐1,5 Mol‐% Li2O dotiertem NiO und an mit 0,05‐2 Mol‐% Ga2O3 dotiertem NiO im Temperaturbereich 50‐200°C (Thermospannung) bzw. 50‐600°C (Leitfähigkeit), gemessen in 1 atm Luft, mitgeteilt. Die Ergebnisse können durch die Halbleitertheorie beschrieben werden: Undotiertes NiO als p‐Halbleiter hat Störstellen mit Akzeptorcharakter (Abstand vom Valenzband 0,75 eV). Durch Dotieren mit Li2O werden Störstellen ebenfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1966
1966
1970
1970

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[7] is inserted ( and finally, we obtain for the lower limit of 4>7 [21] Therefore, the validity of Eq. [18] is given by {3 ze Vo/kT{ 1/6 > ~/7 > 1 [22] From the relation [22], it can be concluded that the 44 rate law is applicable only in a small region of oxide thickness. With the data Vo = iv, Co = 1017 cm -3, = 3, T = 800~ and z = --2, we obtain for By means of these values and Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] is inserted ( and finally, we obtain for the lower limit of 4>7 [21] Therefore, the validity of Eq. [18] is given by {3 ze Vo/kT{ 1/6 > ~/7 > 1 [22] From the relation [22], it can be concluded that the 44 rate law is applicable only in a small region of oxide thickness. With the data Vo = iv, Co = 1017 cm -3, = 3, T = 800~ and z = --2, we obtain for By means of these values and Eq.…”
Section: Discussionmentioning
confidence: 99%
“…With the data Vo = iv, Co = 1017 cm -3, = 3, T = 800~ and z = --2, we obtain for By means of these values and Eq. [22], it can be seen that the law should be obeyed after an oxide thickness of 300A has been built up. Furthermore, the thickness of the oxide layer where the validity of the }4 rate law ceases, should be double the thickness at which it starts, i.e., when the oxide layer has grown approximately by a factor of 2.…”
Section: Discussionmentioning
confidence: 99%